Is soil sampling appropriate for quantitative carbon accounting for biochar? An experimental investigation to assess soil carbon accumulation - David Chiaramonti; Giulia Lotti; Francesca Tozzi; David Casini; Francesco Primo Vaccari; Hamed Sanei; Michaela Luconi; Marco Buffi (Biomass and Bioenergy, 2026)

Italian research and development in space weather and space climate: a state-of-the-art overview - Francesco Berrilli; Marco Casolino; Giuseppe Consolini; Stefania Lepidi; Mauro Messerotti; Roberta Tozzi; Umberto Villante; Francesca Zuccarello (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)
This article presents a concise overview of research developments and advancements in space weather and space climate, with a specific focus on the significant contributions made by members of the Italian Space Weather Community (SWICo). We highlight their achievements in instrument development, observational techniques, and modeling. Furthermore, we introduce a special collection of papers within this journal, entitled “Frontiers in Italian Studies on Space Weather and Space Climate.” This collection features a selection of research articles and presentations from the Second and Third SWICo Congresses, held in Rome in February 2022 and November 2024, respectively, and hosted by the Italian Space Agency.

Assessing marginality of Camelina (C. sativa L. Crantz) in rotation with barley production in Southern Europe: A modelling approach - Calogero Schillaci; Alessia Perego; Marco Acutis; Marco Botta; Tommaso Tadiello; Mara Gabbrielli; Tommaso Barsali; Francesca Tozzi; David Chiaramonti; Arwyn Jones (Agriculture, Ecosystems & Environment, 2023)

Developing patterns in Prunus laurocerasus grown on sediment enriched substrates - Francesca Tozzi; Maurizio Antonetti; Domenico Prisa; Gianluca Burchi; Adelaide Turchi; Cristina Macci; Eleonora Peruzzi; Stefania Nin (Journal of Soils and Sediments, 2022)